2015
DOI: 10.1007/s13404-015-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial exploration of color in gold-based alloys

Abstract: Combinatorial approaches comprised of combinatorial magnetron co-sputtering deposition and fast screening methods are introduced to study color as a function of composition in Au-based alloys. The microstructures of the thin films and bulk alloys are identified by X-ray diffraction, and their colors of the alloys are characterized by optical reflectivity. The results reveal that when comparing microstructures and reflectivity, thin films are similar to bulk alloys. In AuAg-Cu solid solutions, the color of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Therefore, a broad composition range is expected to form glass phase under the high cooling rate during sputtering-deposition32. We recently reported that automated X-ray diffraction (XRD) is capable of maping out the atomic structure of the materials library324. Figure 2(b) shows the XRD spectrum for one of the alloys in the materials library.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a broad composition range is expected to form glass phase under the high cooling rate during sputtering-deposition32. We recently reported that automated X-ray diffraction (XRD) is capable of maping out the atomic structure of the materials library324. Figure 2(b) shows the XRD spectrum for one of the alloys in the materials library.…”
Section: Resultsmentioning
confidence: 99%
“…In order to develop metallic glasses with optimized antibacterial properties, which can be paired with other required properties, novel development strategies are required. Recent investigations indicate that combinatorial approaches are promising in accelerating development of new metallic glasses324252627. Although the combinatorial approach has been used for the development of antibacterial agents in different materials classes282930, its application in metallic alloys remains limited31.…”
mentioning
confidence: 99%
“…The black region represents considered compositions that crystallized, even upon sputtering. The symbols indicate the composition with the highest measured GFA, reported ternary MG compositions with high GFA 21 , 31 and dotted lines indicating a range, reported binary MG compositions 36 , 37 , the global eutectic composition 34 , and the composition with the lowest nucleation temperature 12 . The compositions in all the Gibbs triangles ( a–e ) are in at.%.…”
Section: Resultsmentioning
confidence: 99%
“…2g ). T L is extracted from the ternary phase diagram 34 . As the final result, R C is plotted as a function of composition (Figs 3e and 4a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation